ESTIMATE OF THE WOOD SPECIFIC GRAVITY IN CLONAL HYBRID OF Eucalyptus urophylla x Eucalyptus grandis USING A NON DESTRUCTIVE METHOD - Gonçalves, Fabricio Gomes (2015)
Density is one of the most important properties to the solid wood industries. In this work the specific gravity was indirectly determined using an equipment named Pilodyn. It was also used a resistograph to evaluate the relations between resistance in the shaft penetration and specific gravity of eucalypt wood in three different management systems. The pilodyn penetration didn’t present satisfactory correlation with the specific gravity. Analysis of regression was used to estimate the wood specific gravity. The linear model presented better adjustment (r2 = 34.90%). The measurements made with the resistograph in the pith-bark direction of the trees only allowed to detect the presence of juvenile wood in the treatments. It was not possible to correlate specific gravity with the information generated by the resistograph.